INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BIOLOGI DI ERA DIGITAL - I Gusti Ayu Rai; Gede Prana Jaya (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2026)
The rapid development and advancement of digital technology have brought significant changes to the field of education. On the one hand, digital technology provides considerable benefits by facilitating teachers and students in accessing a wide range of information and pedagogical innovations. On the other hand, it also raises serious concerns, particularly regarding challenges in the formation of students’ character. Character education is a fundamental foundation that must be integrated into all learning processes, with the aim of ensuring that students not only possess strong cognitive competencies but also demonstrate good morals and positive attitudes. This study aims to examine the concept of integrating character education, particularly in biology learning in the digital era. The research employed a literature review method, drawing on various sources such as educational policies, journal articles, and relevant books. The integration of character education in biology learning in the digital era represents a holistic approach that combines mastery of biological concepts, character development, and the cultivation of 21st-century skills in a sustainable manner. The findings indicate that digital technology is not merely a supporting tool but also serves as an effective medium for strengthening students’ character. However, its success largely depends on teachers’ competencies in utilizing technology to design innovative, meaningful learning experiences that are oriented toward character values.